Respect for environment and willingness-to-pay of the customer in the spanish hospitality industry - Sánchez-Ollero, José Luis; García-Pozo, Alejandro; Marchante-Mera, Andrés Jesús (My University, 2014)
Respect for the environment could be a differentiating attribute over competitors and will lead to competitive advantages. Some authors highlight the fact that, providing the environmental setting is valued by clients, it becomes a differentiating output. Other authors consider environmental compliance as an element for improving the quality of the product and an attribute of the service provided by firms that has economic value for the consumer. Currently, environmental responsibility is having an effect on the behaviour of consumers when making purchasing decisions, influencing their reasons for travelling and the final choice of destination and service provider. In this paper we analyze whether environmental variables have an influence in the willingness-to-pay (WTP) of the tourist.
Keywords: Turismo - Aspectos ambientales; Environment; Willingness to pay; Hospitality industry